Roots [videorecording (DVD)] - Haley, Alex (Warner Home Video, 2007)
Follows several generations in the lives of a slave family. The sage begins with Kunta Kinte, a West African youth captured by slave raiders and shipped to America in the 1700s. The family is depicted up until the Civil War where Kunte Kinte's grandson gains his emancipation.